ChemInform Abstract: Thienopyrimidinedione Formation versus Ester Hydrolysis from Ureido Carboxylic Acid Methyl Ester. Issue 26 (6th June 2013) - Reille‐Seroussi, Marie; Labruere, Raphael; Inguimbert, Nicolas; Broussy, Sylvain; Gagey‐Eilstein, Nathalie; Liu, Wang‐Qing; Vidal, Michel; Huguenot, Florent
Abstract The process is studied for a broad spectrum of substrates with respect to product ratio of ester hydrolysis and cyclization to pyrimidinediones.